Analisis Ketepatan Kode Diagnosis Typhoid Fever Pada Rekam Medis Rawat Inap di Rumah Sakit Islam Karawang Tahun 2020 - Nurfena, Deta Nurfena; Indawati, Laela; Dewi, Deasy Rosmala; Fannya, Puteri (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Medical record is a file containing records and documents regarding patient identity, examination, treatment, actions and other services that have been provided to patients. where one of the services provided is the management of patient medical record documents that contain coding of diagnoses and actions given to patients. The implementation of coding disease diagnoses in hospitals is a very important activity, namely by classifying disease diagnoses into several groups for the benefit of reports that the hospital does every month, both for internal reports and external reports and plays an important role in the financing system at the hospital itself. The purpose of this study was to determine the accuracy of the diagnosis code for typhoid fever in inpatients at the Karawang Islamic Hospital. The research methodology was carried out using quantitative descriptive methods, the population was 200 medical records of typhoid fever patients in 2020, with a total sample of 67 samples. The sampling technique used is simple random sampling. How to collect data is done by direct observation. The accuracy of the code obtained is 31 (46%) correct codes and 36 (54%) incorrect codes, the inaccuracy of the code is caused by the medical record professional staff in charge of the coding section who are still not focused and not careful with laboratory results to determine the results of the coding. It is correct and only codes for the H titer, while in determining the diagnosis of typhoid fever, it is seen from the O titer. Suggestions for coding the diagnosis carried out at the Karawang Islamic Hospital are expected that the coding is carried out correctly according to the diagnosis, history, and laboratory results.